The Discovery and Characterization of Targeted Perikaryal-Specific Brain Lesions With Excitotoxins - Coyle, Joseph T.; Schwarcz, Robert (Frontiers in Neuroscience, 2020)
The neurotoxic action of glutamic acid was first described by Lucas and Newhouse, who demonstrated neural degeneration in the inner layers of the neonatal mouse retina after systemic treatment with L-glutamate. Olney extended these findings by showing that neuronal degeneration affected other brain structures including neurons within the arcuate nucleus of the hypothalamus and the area postrema, that the lesion spared axons passing through these areas, and that the neurotoxic potency of glutamate analogs correlated with their excitatory potency, resulting in the designation “excitotoxins.” As this method affected only a small number of brain regions, it was not suitable for targeted brain lesions. The Coyle laboratory showed that direct injection of the potent glutamate receptor agonist, kainic acid, into the rat striatum caused a rapid degeneration of intrinsic neurons while sparing axons of passage or termination including the unmyelinated dopaminergic terminals. Kainic acid also exhibited this perikaryal-specific and axon-sparing profile when injected into the cerebellum, hippocampus and eye. However, neuronal vulnerability was highly variable, with hippocampal CA3, pyriform cortex and amygdala neurons exhibiting great sensitivity due to kainate’s high convulsive activity. In a comparison study, ibotenic acid, a potent glutamatergic agonist isolated from the amanita muscaria mushroom, was found to have excitotoxic potency comparable to kainate but was far less epileptogenic. Ibotenate produced spherical, perikaryal-specific lesions regardless of the site of injection, and experiments with specific glutamate receptor antagonists showed that its effects were mediated by the N-methyl-D-aspartate receptor. Because of this uniform neurotoxicity and near ubiquitous efficacy, ibotenic acid became the excitotoxic lesioning agent of choice. The discovery of the excitotoxic properties of the tryptophan metabolite quinolinic acid and of the anti-excitotoxic, neuroprotective effects of the related metabolite kynurenic acid in the Schwarcz laboratory then gave rise to the concept that these endogenous compounds may play causative roles in the neuropathology of a wide range of neurological and psychiatric disorders.